2016
DOI: 10.1080/10942912.2016.1141296
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Nutritional, Functional, Morphological, and Diffractogram Study on Culinary Banana (MusaABB) Peel at Various Stages of Development

Abstract: The culinary banana peel, which is an agricultural waste available in abundance, has not been able to draw much attention in terms of its utilization. In addition to being an abundant source of functional and nutritional compounds, it also deserves to be utilized in a proper and/or better way. The aim of this study was to explore this agro-waste at different levels of maturity in order to identify the active compounds at particular stage of maturity. Phenolics, flavonoids, and radical scavenging activity were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 52 publications
(59 reference statements)
3
19
1
Order By: Relevance
“…In unripe bananas, starch is one of the main digestible carbohydrates but, during ripening, the starch content decreases while the soluble sugar increases, which occurs due to the action of enzymes that degrade starch and participate in the formation of sugars. 26 According to these results, it was verified that the ripening stage of the fruit influenced the composition of the flour, due to the variations found in this study and those obtained by Angelis-Pereira et al, 34 corroborating with the observation made by Emaga et al 6 Fruit peels have a higher fiber content than the pulp, which is due to their protective function against external threats. 30 The highlight of the ripe banana peel flour obtained was its high content of dietary fiber, with the insoluble portion at highest concentration.…”
Section: Characterization Of Ripe Banana Peel Floursupporting
confidence: 86%
See 3 more Smart Citations
“…In unripe bananas, starch is one of the main digestible carbohydrates but, during ripening, the starch content decreases while the soluble sugar increases, which occurs due to the action of enzymes that degrade starch and participate in the formation of sugars. 26 According to these results, it was verified that the ripening stage of the fruit influenced the composition of the flour, due to the variations found in this study and those obtained by Angelis-Pereira et al, 34 corroborating with the observation made by Emaga et al 6 Fruit peels have a higher fiber content than the pulp, which is due to their protective function against external threats. 30 The highlight of the ripe banana peel flour obtained was its high content of dietary fiber, with the insoluble portion at highest concentration.…”
Section: Characterization Of Ripe Banana Peel Floursupporting
confidence: 86%
“…However, other researchers have obtained better results in comparison to the ones found in this study: in Cavendish banana peel flour, at different ripening stages (590 -2900 mg GAE 100 g -1 ) 26,39 and unripe plantain peel flour (771 mg GAE 100 g -1 ). 29 Therefore, the different results of total phenolic compounds found are influenced by fruit variety, cultivation conditions, Figure 1.…”
Section: Total Phenolic Compounds and Antioxidant Activitycontrasting
confidence: 73%
See 2 more Smart Citations
“…A study by Adeniji et al [27] reported similarly high carbohydrate content in five hybrids of the Musa cultivar. A study by Khawas and Deka [28] also reported substantially high levels of carbohydrates in the peel of culinary banana (Musa ABB with one chromosomal set).…”
Section: Discussionmentioning
confidence: 91%